Assessing the Impact of Environmental Factors on Andipalayam Lake's Insect Biodiversity - Gopalakrishnan, S; J., Jagatheeswari; Nandhini, M (Journal of Zoological Research, 2025)
Andipalayam Lake, a freshwater body located in Tiruppur, Tamil Nadu, plays a significant role in sustaining the local ecosystem, particularly through its diverse insect populations. This study aims to document and analyze the insect biodiversity present in and around Andipalayam Lake, focusing on the ecological roles these species play in maintaining the lake’s health. Insects are key components of aquatic ecosystems, contributing to processes such as pollination and nutrient cycling and serving as prey for higher trophic levels. Despite their ecological importance, studies on the insect biodiversity of Andipalayam Lake have been limited, prompting the need for an extensive survey. This research employed a combination of sweep nets, pitfall traps, and light traps to collect insect species over a year, covering various seasons to capture population dynamics and seasonal variations. Water quality parameters, such as temperature, pH, and dissolved oxygen, were monitored to assess their influence on insect diversity. The study identified over 38 species of insects from diverse orders, including Odonata (dragonflies), Diptera (flies), Coleoptera (beetles), and Hemiptera (true bugs). Seasonal variations were observed, with higher species richness during the monsoon period due to increased vegetation and moisture levels. The most abundant species were found to belong to Diptera and Coleoptera, indicating their adaptability to fluctuating water levels. Environmental factors such as pollution from nearby agricultural runoff and urban development were found to negatively affect insect diversity, with a notable decline in sensitive species during periods of increased contamination.
Keywords: Insect Biodiversity; Andipalayam Lake; Freshwater Ecosystem; Aquatic Insects; Environmental Impact